2007
DOI: 10.2320/matertrans.48.265
|View full text |Cite
|
Sign up to set email alerts
|

Creep and Corrosion Properties of the Extruded Magnesium Alloy Containing Rare Earth

Abstract: Effects of microstructures on the creep and corrosion properties were investigated in the Mg-8Al alloys with addition of the rare earth elements (La-rich Mischmetal, RE). The addition of RE to Mg-8Al alloy may form a stable intermetallic phase, Al 11 RE 3 at elevated temperature, and suppress the phase (Mg 17 Al 12 ) with poor stability at high temperature. The corrosion rate of the alloy slightly decreases with increasing the added RE contents. The constant-load creep behavior was examined at 423, 448 and 473… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Further it can be confirmed that XRD peaks of A 11 MM 3 or Al 4 MM overlaps XRD peaks at 32.4 and 42° and 76° represent A 11 MM 3 or Al 4 MM. 25,26 The formation ability from elements to compound can be evaluated by the electronegativity differences between elements. The larger the electronegativity differences are, the easier the formation of a metallic compound is.…”
Section: Resultsmentioning
confidence: 99%
“…Further it can be confirmed that XRD peaks of A 11 MM 3 or Al 4 MM overlaps XRD peaks at 32.4 and 42° and 76° represent A 11 MM 3 or Al 4 MM. 25,26 The formation ability from elements to compound can be evaluated by the electronegativity differences between elements. The larger the electronegativity differences are, the easier the formation of a metallic compound is.…”
Section: Resultsmentioning
confidence: 99%
“…Of all the materials used to make the vehicle's independent suspension components, magnesium alloys have the lowest density, 1.74 g/cm3, which makes them 35% lighter than aluminum alloys, and over four times lighter than steel [21]. Magnesium alloys are characterized by good ductility, better noise and vibration damping characteristics compared to aluminum alloys, and excellent casting capabilities [22]. The biggest disadvantage of magnesium alloys is their high cost [23].…”
Section: Magnesium Alloysmentioning
confidence: 99%
“…It also has a low elastic modulus, limited fatigue and creep resistance at elevated temperatures, and limited ductility and workability at room temperatures, because of the hexagonal closely packed (HCP) crystal structure [4, 5]. However, these challenges with magnesium are of less importance when compared to its lightweight, excellent specific strength, hot formability, cast‐ability, good ductility, machinability, sound‐damping capabilities, recyclability, and good electromagnetic interference‐shielding [6–9]. Magnesium is the lightest of all lightweight metals used in structural applications, with a density of 1.74 g cm −3 , which is about seventy‐eight percent lighter than steel (density of 7.86 g cm −3 ); and forty‐seven percent lighter than aluminum (density of 2.7 g cm −3 ).…”
Section: Introductionmentioning
confidence: 99%